On lady terminator interview with Barbara Anne Constable - Leavold, Andrew (2014)
Access online through this link: https://www.plarideljournal.org/article/on-lady-terminator-interview-with-barbara-anne-constable
Keywords: Lady Terminator (Film); Motion picture actors and actresses; Constable, Barbara Anne; Constable, Barbara Anne -- Interviews